Markers of HIV infection in the Concorde trial. Concorde Co-ordinating Committee. - Walker, A; Peto, T; Babiker, A; Darbyshire, J (1998)
The Concorde trial compared immediate (Imm) with deferred (Def) AZT monotherapy in asymptomatic HIV-positive participants. Haematological and immunological markers and weight were measured throughout, and correlated with clinical endpoints. Markers associated with disease progression (CD4 lymphocyte count and percentage, platelets, p24 antigen and beta 2 microglobulin favoured Imm: those associated with toxicity (haemoglobin, neutrophils and white cell count) favoured Def. CD8 and total lymphocyte count did not differ significantly between groups. In multivariate analysis, the combination of baseline CD4, p24 antigen and beta 2m was the best baseline predictor of disease. Including change in CD4 and beta 2m at 12 weeks, or changes over follow-up in these markers significantly improved the fit. Markers were also incorporated into the definition of 'clinical' endpoints. Hazard ratio estimates from end-points that included CD4 < 50 and CD4 < 25 were closest to those for AIDS or death alone, but added very few extra events. Use of other landmark CD4 counts (100 or greater) or relative decreases in counts (25% or more) increased the number of events, but overestimated the effect of immediate AZT. Although AZT had a beneficial effect on the surrogate markers of efficacy evaluated, these changes did not predict clinical outcome, nor could the markers be usefully incorporated into an endpoint definition.